ANALISIS FAKTOR YANG BERHUBUNGAN DENGAN PERILAKU IBU HAMIL TENTANG AKTIVITAS SEKSUAL KEHAMILAN DI PUSKESMAS SAMBUTAN SAMARINDA - stephanie stephanie (MMJ (Mahakam Midwifery Journal), 2016)
ABSTRACT Sexual activity is one important partbecause sexual activity is a primary need for married couples. Sexual activity trigged many days of pregnancy although medically related questions during the pregnancy in a safe condition. To determine the factors associated with the behavior of pregnant women about sexual activity during pregnancy in Puskesmas Sambutan Samarinda Sambutan 2014. This study aimed to analyze the analytic because that will be examined. Meanwhile, according of this study using cross sectional approach where subjects were observed only once with the measurement of independent and dependent variables is done at the time of inspection. Research methods using multivariate linear regression. Result of the analysis of the relationship of linear multivariate regression statistical test showed variable calculation Work with P value = 10,868 < 0,05, which means that the independent variable is highly correlated with the dependent so that there is a correlation between behavioral work with pregnant women about sexual activity during pregnancy in Puskesmas Sambutan Samarinda Kalimantan Timur 2014. There is a relationship between tradition, work, attitude and support of health workers with sexual activity during pregnancy and there is no relationship between knowledge, availability of health care facilities. Keywords : Behavior, Pregnancy, Sexual Activity